Divergent Jurisprudential Paradigms of Productive Zakat: A Madhhab-Based Comparative Study of Legal Reasoning in LAZISNU and LAZISMU - Solehudin, Ending; Fautanu, Idzam; Ahyani, Hisam; Masuwd, Mowafg (Mazahibuna: Jurnal Perbandingan Mazhab, 2026)
This study examines productive zakat not merely as a managerial instrument for economic empowerment, but as a manifestation of contemporary Islamic legal ijtihād (independent legal reasoning) shaped by divergent jurisprudential paradigms. Situated within the framework of comparative madhhab studies, this research analyzes how differences in legal reasoning between LAZISNU—rooted in the Shāfiʿī legal tradition—and LAZISMU—characterized by a reformist approach grounded in tajdīd (renewal) and tarjīḥ (legal preference)—influence the formulation and implementation of productive zakat practices in Indonesia. Employing a qualitative juridical-empirical method, the study draws on in-depth interviews with zakat administrators and institutional documents from LAZISNU and LAZISMU operating in Java and Bali. The findings reveal that the transformation of zakat from consumptive distribution to productive utilization is legitimized through distinct modes of istidlāl (legal reasoning or inferential deduction), wherein LAZISNU emphasizes adherence to authoritative Shāfiʿī doctrines, particularly concerning the principle of tamlīk (transfer of ownership to beneficiaries), while LAZISMU adopts a more flexible form of ijtihād that prioritizes maqāṣid al-sharīʿah (the higher objectives of Islamic law) and socio-economic outcomes. This divergence reflects an ongoing dialectic within contemporary Islamic legal thought regarding the boundaries of zakat utilization. By integrating empirical practices with cross-madhhab legal analysis, this study contributes to the development of comparative fiqh al-zakāt (Islamic jurisprudence of zakat) and demonstrates how modern philanthropic institutions negotiate classical legal doctrines within heterogeneous socio-legal contexts such as Java and Bali.